PENGARUH OLAHRAGA JOGGING TERHADAP KADAR HEMOGLOBIN PADA PENDONOR RUTIN DI UDD PMI KABUPATEN LOMBOK BARAT - Samsulhadi, Wiwid; Lentera Afrida Kusumawardani; Kwarta, Cityta Putri; Amalia, Yustisia; Reswari, Putu Ayu Dhana (Jurnal Medicare, 2026)
Maintenance of hemoglobin (Hb) levels in blood is an essential requirement for regular donors to ensure donor eligibility and recipient safety. Observations at UDD PMI West Lombok indicated a high rate of donor disqualification due to low Hb levels. This study aimed to analyze the relationship between jogging activity and Hb levels among regular donors at UDD PMI West Lombok Regency. An analytical observational study with a cross-sectional design was conducted on 91 respondents selected using the Slovin formula. Physical activity data were collected through a Guttman scale questionnaire, while Hb levels were measured using the Hemo Control device. Data were analyzed using the Chi-Square test. The majority of respondents were male (73%), with the dominant age group being 40–49 years (42%). A total of 53% of respondents regularly performed jogging, and 62% had Hb levels within acceptable specifications. The Chi-Square test showed a p-value of 0.001 (<0.05). There was a significant relationship between jogging activity and hemoglobin levels among regular donors.